A web-based approach to measure skill mismatches and skills profiles for a developing country : the case of Colombia - Cárdenas Rubio, Jeisson (Bogotá : Editorial Universidad del Rosario, 2020)
Several interdisciplinary studies highlight imperfect information as a possible explanation of skill mismatches, which in turn has implications for unemployment and informality rates. Despite information failures and their consequences, countries like Colombia (where informality and unemployment rates are high) lack a proper labour market information system to identify skill mismatches and employer skill requirements. One reason for this absence is the cost of collecting labour market data. Recently, the potential use of online job portals as a source of labour market information has gained the attention of researchers and policymakers, since these portals can provide quick and relatively low-cost data collection. As such, these portals could be of use for Colombia. However, debates continue about the efficacy of this use, particularly concerning the robustness of the collected data. This book implements a novel mixed-methods approach (such as web scraping, text mining, machine learning, etc.) to investigate to what extent a web-based model of skill mismatches can be developed for Colombia. The main contribution of this book is demonstrating that, with the proper techniques, job portals can be a robust source of labour market information. In doing so, it also contributes to current knowledge by developing a conceptual and methodological approach to identify skills, occupations, and skill mismatches using online job advertisements, which would otherwise be too complex to be collected and analysed via other means. By applying this novel methodology, this study provides new empirical data on the extent and nature of skill mismatches in Colombia for a considerable set of non-agricultural occupations in the urban and formal economy. Moreover, this information can be used as a complement to household surveys to monitor potential skill shortages. Thus, the findings are useful for policymakers, statisticians, and education and training providers, among others.
PÁGINA LEGAL -- CONTENTS -- LIST OF FIGURES -- LIST OF TABLES -- ACRONYMS AND ABBREVIATIONS -- 1. INTRODUCTION -- 2. THE LABOUR MARKET AND SKILL MISMATCHES -- 2.1. INTRODUCTION -- 2.2. BASIC DEFINITIONS -- 2.3. HOW THE LABOUR MARKET WORKS UNDER PERFECT COMPETITION -- 2.4. MARKET IMPERFECTIONS AND SEGMENTATION -- 2.5. CONCLUSION -- 3. THE COLOMBIAN CONTEXT -- 3.1. INTRODUCTION -- 3.2. THE CHARACTERISTICS OF THE COLOMBIAN LABOUR MARKET -- 3.3. SKILL MISMATCHES IN COLOMBIA -- 3.4. AN INTERNATIONAL EXAMPLE OF SKILL MISMATCH MEASURES -- 3.5. LACK OF ACCURATE INFORMATION TO DEVELOP WELL-ORIENTATED PUBLIC POLICIES -- 3.6. CONCLUSION -- 4. THE INFORMATION PROBLEM: BIG DATA AS A SOLUTION FOR LABOUR MARKET ANALYSIS -- 4.1. INTRODUCTION -- 4.2. A DEFINITION OF BIG DATA -- 4.3. BIG DATA ON THE LABOUR MARKET -- 4.4. POTENTIAL USES OF INFORMATION FROM JOB PORTALS TO TACKLE SKILL SHORTAGES -- 4.5. BIG DATA LIMITATIONS AND CAVEATS -- 4.6. BIG DATA IN THE COLOMBIAN CONTEXT -- 4.7. CONCLUSION -- 5. METHODOLOGY -- 5.1. INTRODUCTION -- 5.2. MEASUREMENT OF THE LABOUR DEMAND: JOB VACANCIES -- 5.3. SELECTING THE MOST IMPORTANT VACANCY WEBSITES IN THE COUNTRY -- 5.4. WEB SCRAPING -- 5.5. THE ORGANISATION AND HOMOGENISATION OF INFORMATION -- 5.6. CONCLUSION -- 6. EXTRACTING MORE VALUE FROM JOB VACANCY INFORMATION -- 6.1. INTRODUCTION -- 6.2. IDENTIFYING SKILLS -- 6.3. IDENTIFYING NEW OR SPECIFIC SKILLS -- 6.4. CLASSIFYING VACANCIES INTO OCCUPATIONS -- 6.5. DEDUPLICATION -- 6.6. IMPUTING MISSING VALUES -- 6.7. VACANCY DATA STRUCTURE -- 6.8. CONCLUSION -- 7. DESCRIPTIVE ANALYSIS OF THE VACANCY DATABASE -- 7.1. INTRODUCTION -- 7.2. VACANCY DATABASE COMPOSITION -- 7.3. GEOGRAPHICAL DISTRIBUTION OF VACANCIES AND NUMBER OF JOBS -- 7.4. LABOUR DEMAND FOR SKILLS -- 7.5. DEMAND BY SECTOR -- 7.6. TRENDS IN THE LABOUR DEMAND -- 7.7. WAGES -- 7.8. OTHER CHARACTERISTICS OF THE VACANCY DATABASE -- 7.9. CONCLUSION -- 8. INTERNAL AND EXTERNAL VALIDITY OF THE VACANCY DATABASE -- 8.1. INTRODUCTION -- 8.2. INTERNAL VALIDITY -- 8.3. EXTERNAL VALIDITY -- 8.4. CONCLUSION -- 9. POSSIBLE USES OF LABOUR DEMAND AND SUPPLY INFORMATION TO REDUCE SKILL (...) -- 9.1. INTRODUCTION -- 9.2. LABOUR MARKET DESCRIPTION -- 9.3. MEASURING POSSIBLE SKILL MISMATCHES (MACRO-INDICATORS) -- 9.4. DETAILED INFORMATION ABOUT OCCUPATIONS AND SKILL MATCHING -- 9.5. CONCLUSIONS -- 10. CONCLUSIONS AND IMPLICATIONS -- 10.1. INTRODUCTION -- 10.2. CONCEPTUAL CONTRIBUTIONS -- 10.3. CONTRIBUTIONS TO METHODOLOGY -- 10.4. EMPIRICAL CONTRIBUTIONS -- 10.5. IMPLICATIONS FOR PRACTICE AND POLICY -- 10.6. LIMITATIONS -- 10.7. FURTHER RESEARCH -- 10.8. CONCLUSIONS -- REFERENCES -- APPENDIX -- APPENDIX A: EXAMPLES OF JOB PORTAL STRUCTURES -- APPENDIX B: TEXT MINING -- APPENDIX C: DETAILED PROCESS DESCRIPTION FOR THE CLASSIFICATION OF COMPANIES -- APPENDIX D: MACHINE LEARNING ALGORITHMS -- APPENDIX E: SUPPORT VECTOR MACHINE (SVM) -- APPENDIX F: SVM USING JOB TITLES -- APPENDIX G: NEAREST NEIGHBOUR ALGORITHM USING JOB TITLES -- APPENDIX H: ADDITIONAL TABLES.
Incluye referencias bibliográficas.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2022. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Agentes de empleo; Skilled labor -- Colombia; Labor market -- Colombia -- Statistics; Desarrollo de páginas web; Mercado laboral -- Innovaciones tecnológicas -- Colombia; Procesamiento de la información.; Web -- Minería de datos; Libros electrónicos.